2015
DOI: 10.1007/s00442-015-3480-6
|View full text |Cite
|
Sign up to set email alerts
|

Transgenerational effects of land use on offspring performance and growth in Trifolium repens

Abstract: offspring, but this was not the case in the other treatments. When grown among or in close proximity to competitors, T. repens plants did not show preferential growth towards open spaces (i.e., no horizontal foraging), but did show strong vertical foraging by petiole elongation. In the homogeneous competition treatment, petiole length increased with the productivity of the parental site, but this was not the case in the heterogeneous competition treatment. Moreover, petiole length increased with mowing frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…However, the process of plasticity recovering to normal for maintained dwarf phenotype of L. chinensis warrants more detailed studies that utilize greenhouse experiments observed for several clonal generations. Also, more and more evidence of epigenetic inheritance in molecular biology has shown that histone variants, histone N-tail modifications, and DNA methylation affected the expression not only of within-generation phenotypic plasticity but also of transgenerational phenotypic plasticity (Iwasaki, 2015; Herman and Sultan, 2016; Wang et al, 2016). These previous empirical and theoretical studies have provided direct or indirect support for the type of phenotypic plasticity observed in L. chinensis in this study.…”
Section: Discussionmentioning
confidence: 99%
“…However, the process of plasticity recovering to normal for maintained dwarf phenotype of L. chinensis warrants more detailed studies that utilize greenhouse experiments observed for several clonal generations. Also, more and more evidence of epigenetic inheritance in molecular biology has shown that histone variants, histone N-tail modifications, and DNA methylation affected the expression not only of within-generation phenotypic plasticity but also of transgenerational phenotypic plasticity (Iwasaki, 2015; Herman and Sultan, 2016; Wang et al, 2016). These previous empirical and theoretical studies have provided direct or indirect support for the type of phenotypic plasticity observed in L. chinensis in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Clonal propagation in general is a common adaptation of species that grow in frequently mown or grazed habitats (Wellstein & Kuss, 2011), yet within-species adaptive differentiation in ability of clonal reproduction was so-far only rarely documented (e.g. Simon-Porcar et al, 2021; Wang et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…They demonstrated that stomatal development under different environmental conditions can be induced by changes in DNA methylation status due to the climate change. It was also found that the stomatal traits could be transgenerationally heritable under environmental stress in Arabidopsis thaliana in response to drought 41 and their development was shown to be under epigenetic control 95 . Stomata traits could also be genetically adapted to different climatic conditions of plant origin 45 , 96 , 97 .…”
Section: Discussionmentioning
confidence: 99%